Intensity of Basal Stem Rot Disease by Ganoderma in Oil Palm Plantations on Peatlands and Minerals - Herry Wirianata; Fariha Wilisiani; Sri Gunawan; Yefta Mahardika (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Basal stem rot caused by Ganoderma boninense is the main disease of oil palm plantations. The disease decreases yield, causes plant death, shortens economic life, and accelerates replanting. The purpose of this study is to compare the development of this disease in third-generation oil palm plantations in peat soil and mineral soils. Observations were made to verify secondary census data for 4 years on affected (endemic) rotten stems. Observations were made on each of the 3 blocks for peat soil and mineral soil with palm oil planting year 2011-2012. The results showed that stem base rot develops faster with a higher severity in peat soil than yellow-red podsolic soil. The availability of organic matter in both soil and oil palm plant residues becomes an important source of nutrients for pathogenic fungi in completing the cycle of disease in plantations.